2013
DOI: 10.2143/acb.3233
|View full text |Cite
|
Sign up to set email alerts
|

PRIMARY ANTIMICROBIAL RESISTANCE OFHELICOBACTER PYLORIIN BELGIUM

Abstract: The increasing antimicrobial resistance of Helicobacter pylori jeopardizes the efficiency of the classical eradication triple therapy. In this article we assessed the primary resistance rates of Helicobacter pylori to the commonly used antibiotics for eradication in the area of Brussels and determined prospectively, through a questionnaire, the possible risk factors for resistance. Gastric biopsies were taken for histology and culture in all adult patients in whom Helicobacter pylori was searched from February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…This was corroborated by a Brazilian study . However, it was in contrast to other studies from outside the Latin America region that showed rising resistance rates to certain antibiotics over time, especially with regard to levofloxacin resistance . Regarding secondary resistance, a large German study of over 5000 strains found this to be also a major problem, especially with reference to fluoroquinolones.…”
Section: Resistancesupporting
confidence: 55%
See 1 more Smart Citation
“…This was corroborated by a Brazilian study . However, it was in contrast to other studies from outside the Latin America region that showed rising resistance rates to certain antibiotics over time, especially with regard to levofloxacin resistance . Regarding secondary resistance, a large German study of over 5000 strains found this to be also a major problem, especially with reference to fluoroquinolones.…”
Section: Resistancesupporting
confidence: 55%
“…There were many studies on H. pylori resistance levels in the last year. These studies on resistance over the last year are summarized in Table 2 [54][55][56][57][58][59][60][61][62]. One of the most significant of these was a systematic review of studies on resistance in Latin American countries [54].…”
Section: Resistancementioning
confidence: 99%
“…In 2014, 10.1% of H. pylori strains were resistant to clarithromycin in Germany, 9% in Iceland, and 13.3% in Belgium. [25][26][27] In the United States in 2009-2013, 16.4% strains were resistant to clarithromycin, 28 28.1% of strains were resistant to clarithromycin in Bulgaria in 2015, 29% and 38.5% strains were resistant to clarithromycin in Japan in 2013-2014. 29 In Italy in 2016, 72.4% of isolates were resistant to clarithromycin, 30 9.6% and 4% strains were resistant to levofloxacin in Germany and Iceland, respectively.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…25,26 Reported rates of resistance to metronidazole in different countries were: Japan (3%), Iceland (1%), United States (20.3%), Belgium (26.1%), Bulgaria (33.8%), and Italy (34.7%). [26][27][28][29][30][31] In conclusion, H. pylori resistance to clarithromycin remained low substantially between 2009 and 2017, so we suggest using bismuthcontaining quadruple regimen but not levofloxacin-based triple therapy as a second-line empiric treatment.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…On the other hand, antibiotic resistance should not be underestimated. Primary clarithromycin resistance for Europe is reaching 17.6% [29], for metronidazole it is 26%, while for amoxicillin is below 1% [30]. Data from a national study analyzing the prevalence of multidrug-resistant H. pylori in Bulgaria showed that resistance to clarithromycin, metronidazole and amoxicillin was 18.4%, 26.5% and 4.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%